Avaliação da expressão gênica da cápsula articular na instabilidade anterior traumática do ombro - Belangero, Paulo Santoro [UNIFESP] (2016)
The shoulder is the human joint most susceptible to dislocations, with an estimated incidence of 8.2 to 23.9 cases per 100,000 individuals per year. Molecular studies related to shoulder instability could promote a better understanding of the pathophysiology of the disease. We hypothesize that the expression of genes related to collagen, regulating their fibrils and extracellular matrix-related genes might be involved in traumatic anterior shoulder instability and clinical aspects, such as severity and duration of disease. Thus, our objectives were to assess the gene expression in the shoulder joint capsule of patients with traumatic anterior instability and controls, relating them to clinical and etiological aspects. We studied 31 patients with traumatic anterior instability of the shoulder and eight control subjects (patients with acromioclavicular dislocation). Three regions of the capsule were collected: anterior, anterosuperior and posterior. The gene expression was quantified by qRT-PCR. We found alteration of gene expression of three groups: a) collagen encoders; b) regulating gene expression and fibril structure of collagen and c) genes of extracellular matrix; in the three capsular regions studied in the patients with traumatic anterior shoulder instability, including posterior region. The differences were most significant in the anterior region, macroscopically affected region, however the presence of alterations in the posterior region represented the most surprising positive result. Comparing cases and controls, COL1A1, COL1A2, COL3A1, COL5A1 (collagen genes), TGFB1, TGFBR1, PLOD2, COMP (genes related to the formation of collagen fibrils -crosslink) and FN1, TNC and TNXB (related genes extracellular matrix) shown to be differentially expressed and, therefore, may be relevant to the pathophysiology of traumatic shoulder instability. Regarding the duration of disease, COL1A1, TGFB1, TGFBR1, PLOD2, FN1 and TNXB were different and thus may be related to disease progression. Regarding the number of episodes, TGFBR1, PLOD2, LOX, FN1 COL1A1, COL3A1, COL5A1, were different and can also be associated with gravity. Our findings demonstrate that gene expression is involved to the structure and / or maintenance of the glenohumeral capsule individuals with traumatic anterior instability. These changes occur even after a single episode of dislocation and are related to clinical situations that represent disease severity, as the number of episodes of dislocation and time duration of the disease. This was the first study of gene expression in the articular capsule of the shoulder and our data contribute to the understanding of the mechanisms involved in the pathophysiology of the disease that, in a future might help develop new strategies for diagnosis or even treatment by identifying new therapeutic targets.